Health issues and awareness, and the significant of green space for health promotion in Malaysia - Mansor, Mazlina; Harun, Nor Zalina (Elsevier, 2014)
A rise in non-communicable diseases (NCDs) is predominantly due to unhealthy urban lifestyle (e.g. work stress, being sedentary and unhealthy eating habits. This paper identifies health issues in Malaysia, and it reviews preventive measures to make people aware of the importance of healthy living. The paper contends that green space is beneficial, which encourage people to make good choices about their health. It reviews, researches that show that green space support greater outdoor activities and influence healthy behaviors. Thus, green space in the built environment is a significant health promotion agenda that improves the urban quality of life.